Structural phase transitions of syndiotactic polystyrene - Gowd, E. Bhoje; Tashiro, Kohji; Ramesh, C. (Progress in Polymer Science, 2009)
Syndiotactic polystyrene (sPS) exhibits four crystal modifications (alpha, beta, gamma, and delta), along with intermediate forms with different molecular conformations, as well as different chain-packing structures. The extensive literature on the crystal structures exhibited by sPS is reviewed herein, including, the mechanisms of phenomena such as solvent-induced crystallization, thermally induced crystallization and gelation, and the phase transitions among the various crystalline forms. The latter have been studied by static and dynamic wide-angle and small-angle X-ray scattering, infrared and Raman spectra, and neutron scattering, etc., in addition to computer simulations. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: crystal structure; Gelation; phase transition; polymorphism; Solvent-induced crystallization; Syndiotactic polystyrene